Book Review: Chinese in the Post-Civil War South; a People Without a History - Thompson, C Michele (The Southern Historian, 1985)
Keywords: book.review; dept.his

A Biography of Ferdinand and Isabella. - Stewart, Paul (1989)
Keywords: dept.his; faculty_collection; sabbatical_report

Leonard Bacon. - Davis, Hugh (1988)
Keywords: dept.his; faculty_collection; sabbatical_report

Failure of Democracy: Human Rights in the People's Republic of China. - Lee, Ta-ling (Spring; History., 1988)
Keywords: dept.his; faculty_collection; sabbatical_report

One Step Forward, One Step Back: Human Rights in the People's Republic of China in 1987/88 - Copper, John Franklin (School of Law, University of Maryland, 1989)
Keywords: 1976-2002; China; China; Human rights; Politics and government; dept.his; faculty_collection

Africans and Europeans in West Africa: Elminans and Dutchmen on the Gold Coast During the Eighteenth Century - Feinberg, Harvey M. (American Philosophical Society, 1989)
SCSU Faculty Scholar Award
Keywords: Dutch; Ghana; Elmina (Ghana); History; award_winner; dept.his; faculty_collection

Fairfield: The Biography of a Community, 1639-1989 - Farnham, Thomas J. (Published for the Fairfield Historical Society by Phoenix Pub., 1988)
Keywords: Fairfield (Conn.); History; dept.his; faculty_collection

Student Protests in Connecticut Colleges and Universities, 1701-1870: Yale College as a Case Study - Purmont, Jon Emmett (Thesis Ph. D.–Columbia University., 1988)
Keywords: Case studies; Education; Higher; Connecticut; History; History; Students; Political activity; Yale University; dept.his; faculty_collection

Reform in Reverse: Human Rights in the People's Republic of China, 1986/1987 - Lee, Ta-ling; Copper, John Franklin (School of Law, University of Maryland, 1987)
Keywords: China; Human rights; dept.his; faculty_collection

Manifest Destinies: The Usa, the Ussr - Mintz, Max M.; Bennet, John (Boston Pub. Co. ; Distributed by Field Publications, 1987)
Keywords: History; History; Russia; History; Soviet Union; United States; dept.his; faculty_collection

Upper State Street 1640-1982 - Farnham, Thomas J. (s.n., 1983)
Keywords: New Haven (Conn.); Streets; Upper State Street; dept.his; faculty_collection

Vigil in Benicarló - Azaña, Manuel (Fairleigh Dickinson University Press, 1982)
Keywords: Civil War; 1936-1939; Drama; History; Spain; dept.his; faculty_collection

Hmong and Yao: Mountain Peoples of Southeast Asia - Hamilton-Merritt, Jane (SURVIVE, 1982)
SCSU Faculty Scholar Award
Keywords: Hmong (Asian people); Yao (Southeast Asian people); Chemical warfare; award_winner; dept.his; faculty_collection

My First Days of School - Hamilton-Merritt, Jane (Simon & Schuster, 1982)
Five-year-old Kate relates the experiences of her first day in kindergarten.
Keywords: dept.his; faculty_collection

Our New Baby - Hamilton-Merritt, Jane (J. Messner, 1982)
Follows the experiences and changing feelings of a child during a year when a new baby becomes a part of his family.
Keywords: Infants; Juvenile literature; Juvenile literature; Parent and child; Juvenile literature; Siblings; dept.his; faculty_collection

Superpowers, the USA, the USSR - Mintz, Max M.; Bennet, John (HBJ Press, 1980)
Keywords: History; History; Soviet Union; United States; dept.his; faculty_collection

The nature of geography and the Schaefer-Hartshorne debate - Martin, G.J. (Reflections on Richard Hartshorne's "The nature of geography', 1989)
The tendency by geographers to cast Hartshorne as either hero or villain in modern American geography is clearly represented in this essay considering the Hartshorne-Schaefer controversy, a dispute of almost mythical proportions in the modern history of American geography. Through analysis of unpublished and published documents, the author provides us with a wealth of historical information concerning the relation between the two antagonists and the events surrounding the publication of their methodological statements. The reportage has an additional, illocutionary impact that derives from the introduction of historical specificities into the discussion of mythologized events. The description and evaluation of the events surrounding this episode in American geography, especially its portrayal of spatial analysts in the uncharacteristic role of loyal sentimentalists, will probably add fuel to the dying embers of this controversy. -from Editors
Keywords: American geography; Hartshorne; R.; Schaefer; dept.egm; geographers; historical information; illocutionary impact; methodological statement; spatial analysts; ⛔ No DOI found

Access to archives and privacy: The twenty-third international archival round table conference proceedings - Newhall, A.C. (American Archivist, 1989)
1 citations (Crossref) [2023-10-31]
Keywords: dept.his

Eliade, Joyce, and the Terror of History - Forbes, Robert P. (CrossCurrents, 1986)
Keywords: dept.his; ⛔ No DOI found

Book Review: Gamaliel bailey and antislavery union. by stanley harrold. (kent: kent state university press, 1986. xvi + 301 pp. 28.00.) - Davis, Hugh (The Journal of American History, 1988)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/017-531-054-257-566 tex.type: [object Object]
Keywords: book.review; dept.his

Review of Explaining Religion: Criticism and Theory from Bodin to Freud - Ausmus, Harry J. (The American Historical Review, 1988)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1988R305800016 tex.unique-id: [object Object]
Keywords: dept.his

Review of Henry David Thoreau: A Life of the Mind, Robert D. Richardson, Jr - Caruthers, J. Wade; Richardson, Robert D. (The American Historical Review, 1987)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1987L308800157 tex.unique-id: [object Object]
Keywords: dept.his

Review of Religion in the Age of Romanticism: Studies in Early Nineteenth-Century Thought - Ausmus, Harry J. (The American Historical Review, 1986)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1986F313200044 tex.unique-id: [object Object]
Keywords: dept.his

Review of The Seven Day Circle: The History and Meaning of the Week - Ausmus, Harry J. (The American Historical Review, 1986)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1986D315000015 tex.unique-id: [object Object]
Keywords: dept.his

Research in South Africa: to know an archive - Feinberg, Harvey M (History in Africa, 1986)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-439-470-300-398 tex.type: [object Object]
Keywords: dept.his

Review of L'ordre du temps - Ausmus, Harry J. (The American Historical Review, 1985)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1985ASN9100005 tex.unique-id: [object Object]
Keywords: dept.his

Western religious thought - Ausmus, Harry J (Journal of the American Academy of Religion, 1982)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/075-157-295-827-36X tex.type: [object Object]
Keywords: dept.his

Review of Transcendentalism as a Social Movement, 1830-1850 - Caruthers, J. Wade (The American Historical Review, 1982)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1982PT98500167 tex.unique-id: [object Object]
Keywords: dept.his

Nuclear-weapons and the future - an unthinkable proposal - Tyler, RL (Humanist, 1982)
tex.unique-id: ISI:A1982PN18700002
Keywords: dept.his; ⛔ No DOI found

Book Review: Revolution and tradition in tientsin, 1949-1952 - lieberthal,kg - Lee, TL (American Historical Review, 1981)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1981LP78100116
Keywords: book.review; dept.his

High noon in memory lane - the superior reality of the past - Tyler, RL (Humanist, 1981)
tex.unique-id: ISI:A1981LL35600027
Keywords: dept.his; ⛔ No DOI found